Profil Kemampuan Komunikasi Matematis Siswa Kelas VIII Pada Penyelesaian Soal Cerita Materi Sistem Persamaan Linear Dua Variabel - Apriasari, Marfu'ah; Rejeki, Sri (Universitas Negeri Surabaya, 2020)
This study aims at analyzing students' mathematics communication ability in solving word-context problems in the topic of Linear Equation System with Two Variable and describing students' profiles in each level of mathematics communication ability in solving word-context problems in the topic of Linear Equation System with Two Variable using Polya steps. This study is a descriptive qualitative study involving 20 students of grade 8th. The data collection was conducted by using observation, test, interview, and documentation. The data analysis was conducted in three stages, namely data reduction, data display, and conclusion drawing. The results showed that: (1) Students at the low level of mathematics communication ability were only able to complete some Polya steps. The step of understanding the problem, compiling, and carrying out the plan was done poorly. Whereas the action of checking the answers was not completed. (2) Students at the level of mathematics communication ability can write down steps to understand the problem quite well. However, the stages of devising a plan, carrying out the plan, and re-checking answers cannot be done well. (3) Students at a high level of mathematics communication ability can perform the four steps of Polya even though there are still shortages in doing the calculations to get answers.